2017
DOI: 10.1097/sih.0000000000000254
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Clinical Skills Performance of Graduating Medical Students Using “WISE OnCall,” a Multimedia Educational Module

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…As BBN is not a required skill for EPs, it would be interesting to investigate whether BBNSBT is feasible and effective in other areas such as obstetrics, intensive care units, etc. Finally, we think that e-learning preparation before BBNSBT, as described for a training on managing low urine output,58 could replace some of the in-person time.…”
Section: Discussionmentioning
confidence: 99%
“…As BBN is not a required skill for EPs, it would be interesting to investigate whether BBNSBT is feasible and effective in other areas such as obstetrics, intensive care units, etc. Finally, we think that e-learning preparation before BBNSBT, as described for a training on managing low urine output,58 could replace some of the in-person time.…”
Section: Discussionmentioning
confidence: 99%
“…Interest in the academic field of study is one of the important and influential factors in becoming a professional in education and the formation of a professional commitment (14,18). A study on the barriers to achieving professional ethics showed that inappropriate attitude toward the aca-demic discipline leads to lack of motivation and interest (32). According to the findings, public health personnel have a negative attitude to their academic field of study in terms of the social and financial status associated with it.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of an individual's specialty on the applicability of the education and training is accounted for by the relationships among the field of study, professional knowledge and skills and the area of work of the person with the target course of study. The closer this relationship is, the more applicable the education would be (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…This WISE-MD tool is used to give a computerized linear description of the patient and the patient-physician interaction from the first visit of patient, diagnostic process, laboratory studies and finally to the postoperative visits. 8,9 BioDigital Human -ICT Tool: The BioDigital Human is a 3D platform that gives easy understanding of human anatomy and disease conditions to the health professionals. Benefit of this tool is to use online Human Studio models and save models in your account, share with others health professionals.…”
Section: Wise-md (Web-based Initiative In Surgical Education) -Ict Toolmentioning
confidence: 99%